Catecholamines in neuroblastoma: Driver of hypertension, or solely a marker of disease?. Issue 8 (6th October 2021) - Harding, Matthew; Deyell, Rebecca J.; Blydt‐Hansen, Tom
Abstract: Background: Neuroblastoma is a common solid tumor of childhood and is often associated with hypertension. Potential etiologies contributing to hypertension include renal compression, pain, volume overload, and catecholamine secretion. Cases: We completed a single center retrospective review of children with neuroblastoma and ≥stage II hypertension (per Hypertension Canada guidelines) over a 2‐year period. All patients ( n  = 10) had elevated urine normetanephrine levels and eight had intra‐abdominal tumors. Four patients had refractory hypertension requiring > three agents, of which three required alpha/beta blockade. Conclusion: Although multifactorial, hypertension in neuroblastoma often has a neuroendocrine component. Excess normetanephrine production in neuroblastoma may be a more common hypertensive mechanism than previously appreciated. Urinary normetanephrine elevation could suggest potential neuroendocrine‐mediated hypertension.